Strong Vertex Coloring in Bipolar Fuzzy Graphs - Mohamed, S. Yahya; Subashini, N. (Communications in Mathematics and Applications, 2022)
Bipolar fuzzy graph (BFG) coloring techniques are used to solve many complex real world problems. The chromatic number of complement of BFG is obtained and compared with the chromatic number of the corresponding BFGs. This paper is an attempt to define coloring in a BFG based on strong edges. The strong chromatic number of complete BFG and BF tree are obtained.
Keywords: Bipolar fuzzy graphs; Bipolar Fuzzy Sets (BFS); Coloring; Strong edges and strong chromatic number